Sistem Interaktif Siswa Menyimak Asik (SISMA) Berbasis Media QR Code Untuk Meningkatkan Keterampilan Menyimak Siswa Sekolah Dasar - Pinasti, Rachma Indria; Rahmawati, Fitri Puji (STKIP Singkawang, 2024)
This study aims to describe the implementation of the Student Interactive System for Listening Fun (SISMA) based on QR Code as an innovation in interactive and effective learning media for elementary school students. The method used is descriptive qualitative, data was collected through observation, interviews and documentation at SDN Kasreman 3 Ngawi. The results of the study describe that the implementation of SISMA improves students' concentration and understanding in listening activities in class and encourages flexible independent learning that can be accessed anytime and anywhere. The QR Code that is created can attract students to increase listening activities because it is interesting, by being able to be accessed anytime and anywhere, students' understanding of listening activities increases and some students can retell or in writing. SISMA uses QR Code media that can provide quick access to interactive audio learning materials to improve students' listening skills in a more interesting and effective way. The use of SISMA technology based on QR Code media makes it easier to access listening activities for teachers and students. However, there are obstacles such as the availability of adequate devices and internet connection problems.